PERANCANGAN SISTEM INFORMASI PERHITUNGAN PERJALANAN DINAS PADA BALAI WILAYAH SUNGAI KALIMANTAN III BERBASIS WEB - Sari , Marshelina Putri Permata; Wulandari, Phaureula Artha; Bahit, Muhammad (Prosiding Seminar Nasional Manajemen, Ekonomi dan Akuntansi, 2021)
Computers are an alternative in this day and age to perform data processing systems. There are so many benefits of computers in agencies and companies, especially for the administrative and financial fields within agencies or companies in order to make office work more efficient and effective, such as making an Official Travel Order (SPPD) using a computer system. So far, the Office of the Kalimantan River Basin III in making the SPPD has not fully used the system, so that it has an impact on the service and reporting of the annual SPPD. This study aims to create a web-based SPPD to speed up the process of making SPPD and annual reports. The research method used is research and development/R&D with a case study at the Kalimantan River Basin III. The results of this study indicate that using a web-based SPPD can speed up the process of making SPPD and make it easier to make annual reports. Keywords: Business Travel Calculation